Efficacy, Safety, and Cost-Minimization Analysis of Continuous Infusion of Low-Dose Gemcitabine Plus Cisplatin in Patients With Unresectable Malignant Pleural Mesothelioma - Arrieta, Oscar; Muñoz-Montaño, Wendy; Muñiz-Hernández, Sae; Campos, Saul; Catalán, Rodrigo; Soto-Molina, Herman; Guzmán Vázquez, Silvia; Díaz-Álvarez, Osvaldo; Martínez-Pacheco, Victor; Turcott, Jenny G.; Ramos-Ramírez, Maritza; Cabrera-Miranda, Luis; et al. (Frontiers in Oncology, 2021)
Background: Malignant pleural mesothelioma (MPM) is rare and aggressive neoplasia, with a poor prognosis; furthermore, the monetary cost of its treatment represents a major challenge for many patients. The economic burden this malignancy imposes is underscored by the fact that asbestos exposure, which is the most frequent risk factor, is much more prevalent in the lower socioeconomic population of developing countries. The aims of the present study were to evaluate the efficacy, safety, and cost of continuous infusion of low-dose Gemcitabine plus Cisplatin (CIGC) as a treatment strategy for patients with unresectable MPM. Methods: We performed a prospective cohort study to determine efficacy and safety of continuous infusion gemcitabine at a dose of 250 mg/m2 in a 6-hour continuous infusion plus cisplatin 35 mg/m2 on days 1 and 8 of a 21-day cycle in patients with unresectable MPM. We also performed a cost minimization analysis to determine if this chemotherapy regimen is less expensive than other currently used regimens. Results: The median number of chemotherapy cycles was 6 (range 1 – 11 cycles); objective response rate was documented in 46.2%, and disease control rate was seen in 81.2%. Median PFS was 8.05 months [CI 95% 6.97-9.13]; median OS was 16.16 months [CI 95% 12.5-19.9]. The cost minimization analysis revealed savings of 66.4%, 61.9% and 97.7% comparing CIGC with short-infusion gemcitabine plus cisplatin (SIGC), cisplatin plus pemetrexed (CP), and cisplatin plus pemetrexed and bevacizumab (CPB), respectively. Furthermore, this chemotherapy regimen proved to be safe at the administered dosage. Conclusion: CIGC is an effective and safe treatment option for patients with unresectable MPM; besides, this combination is a cost-saving option when compared with other frequently used chemotherapy schemes. Therefore, this treatment scheme should be strongly considered for patients with unresectable MPM and limited economic resources.